Assessing numeracy skills on flat shapes and scaffolding forms in junior high school - Setiyani Setiyani; Stevanus Budi Waluya; Yohanes Leonardus Sukestiyarno; Adi Nur Cahyono; Dina Pratiwi Dwi Santi (Institute of Advanced Engineering and Science, 2024)
Based on The Regulation of The Minister of Education, Culture, Research and Technology No.17 of 2021, cognitive learning outcomes consist of literacy and numeracy as measured through a minimum competency assessment (MCA) with grade 5, 8, and 11. The subjects in this study are 42 students of grade VIII (second grade) from state Junior High School 4 Cirebon and State Junior High School 2 Cirebon, Indonesia. The instruments were tests of numeracy literacy skills, documentation, and interviews. Purposive sampling was used to determine the subject of analysis of test results and interviews. The data were analyzed descriptively through the following stages: data reduction, data presentation, and conclusions drawing. The results showed that the research subjects are still not familiar with numeracy literacy questions which have the characteristics of always being preceded by texts, not understanding what is known and asked in the questions so they tend to blindly guess the answers and needed to be reminded of the prerequisite material. Based on the results of this study, teachers can develop learning media, project-based learning, scaffolding, and teaching materials that accommodate numeracy skills or differentiated learning.